Dakwah di Tengah Industrialisasi Media - el Ishaq, Ropingi (Jurnal Komunikasi Islam, 2013)
This article discusses the position of proselytizing in the middle of the media industry and how this prose–lytizing should be undertaken. This paper argues that the religious contents of publication and broadcast by the mass media tend to be commodified in order to meet the needs of the society, while people use the media for entertainment purposes only. As a result, the content of religion in the media cannot be separated from the element of entertainment. Religion in the media tends to become merely the point entertainment, so that the element of proselytizing and motivation to raise religious awareness tends to be neglected. The purpose of the media as a medium of information, education, edu–tainment, and a tool of social cohesion have not been rea–lized in the current era.Keywords: proselytizing, media industry, media content, the structuration of religion.------------------------------------------------------------------------Artikel ini membahas bagaimana posisi dakwah di tengah industri media dan bagaimana dakwah harus dila–kukan. Tulisan ini berpendapat bahwa konten agama yang dimuat dan ditayangkan oleh media massa cenderung sebagai komoditi untuk memenuhi kebutuhan masyarakat. Sementara masyarakat memanfaatkan media sebagai alat untuk memperoleh hiburan belaka. Alhasil, konten agama dalam media tidak dapat dilepaskan dari unsur hiburan. Agama di media menjadi materi hiburan belaka, sehingga unsur dakwah dan motivasi untuk memunculkan kesadaran beragama menjadi terabaikan. Tujuan media sebagai media informasi, edukasi, hiburan yang mendidik, dan sebagai alat perekat sosial menjadi gagasan yang melangit dan belum terwujud di era demokratisasi media saat ini.Kata Kunci: dakwah, industri media, konten media, strukturasi agama.